Analisis Pengaruh Profitabilitas, Cash holding, dan Likuiditas terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Aini, Nur; Syaiful (Journal of Culture Accounting and Auditing, 2026)
This study analyzes the effects of profitability, cash holdings, and liquidity on firm value, with firm size as a moderating variable, among manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange during the 2024–2025 period. Using a quantitative approach with purposive sampling, 72 observations were obtained and analyzed via Moderated Regression Analysis (MRA) using IBM SPSS Statistics 27. The test results show that profitability, cash holdings, and liquidity were not found to have a significant effect on firm value, indicating that investors place greater emphasis on earnings sustainability, governance quality, and long-term growth prospects than on these indicators individually. In terms of moderation, firm size was not found to moderate the effects of profitability, cash holdings, or liquidity on firm value. These findings suggest that the financial signals transmitted through these three variables are not yet strong enough to influence investor perceptions, regardless of the company’s size.